Maximisation des revenus et du rendement financier par l'optimisation de l'information, de la planification et des pratiques minières (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
During the past 10 years, research work to improve the survey of stope limits after mining supplied useful information, particularly for large open and sub-level stopes, regarding waste dilution caused by differences between final production limits and planned stope limits. However, the efficiency of this information to improve the overall efficiency of the mining process is limited, given that the impacts of inaccurate ore limits leading to dilution (sensu stricto) and ore losses haw not been considered adequately. Geological/sampling information should be optimized in terms of quantity and/or quality for the deposit characteristics and the constraints of the mining method used. As industry practice regarding the definition and recording of dilution is flexible and as ore losses frequently am poorly doc-umented, the use of these terms is reviewed. Simulations were carried out on two typical narrow gold deposits, based on an earlier study at Inco's Thompson mine regarding the impacts of wide to narrow delineation grids using recorded variations of vein geometry. Vertical to sub-vertical deposits of 3 m and 6 m widths mined by long-hole open stopes were considered. Deposits delineated by 7.5 m (25 ft) grids were taken as a base case and the impacts of less accurate limits in conjunction with long hole mining based only on a 15 m (50 ft) delin¬eation grid. The impacts of overestimation (dilution) and underestimation (metal losses) were considered separately, using the average error of +/-0.62 m recorded in the Inco study. The impact of less accurate information was much stronger on the narrower deposit: both dilution and ore losses diminished the net present value of the 3 m wide deposit by 39.27% and 45.41%, respectively, and that of the 6 m wide deposit by 12.84% and 11.55%. As the impacts of ore loss and those of dilution on the net present value am almost identical in these simulations, we could, in practice, assume a 50/50 split between dilution and ore losses in such a case. These results do no take into account the effects of local optimization measures taken at the mine production level (blasthole sampling near stope limits, etc.) The potential impacts of geological and sampling uncertainties in terms of lower NPV justify and require more systematic efforts to ensure that deposit appraisal work and feasibility studies are adequate to optimize company revenue and competitive returns to investors from mine production activities.